From the Page to the Stage. "Musical Topics and Musical Performance' Edited by Julian Hellaby - Baltuch, David (Res Facta Nova, 2025)
The present review summarizes and discusses Musical Topics and Musical Performance published by Routledge and edited by Julian Hellaby. Ten chapters by ten different authors revolve around the concept of musical topic, which may be loosely defined as an ‘object’ of which the music is the ‘sign’. Music may refer to dances (e.g. waltz), moods (e.g. agitato), types of music (e.g. fanfares), periods/styles of music (e.g. archaic) and other referents. The term ‘topic’ has substantially evolved since its creation by Leonard Ratner in 1980, notably though the writings of Raymond Monelle (2000), Robert Hatten (2004) and Eero Tarasti (2012). The authors of this book connect, in their studies, topical analyses of given works to their musical performances, or discuss more broadly a composer’s output or the possible implementations of topical analysis. Connecting music analysis to performance is not an easy task and the journey from theory to practice requires favourable conditions to be successful. Furthermore, musicological texts that would happily reach an audience of practising performers are difficult to produce, not only because the mindsets and aims of musicologists and performers are different but also because each domain works with a specialized vocabulary that is not always shared by the other domain. Nonetheless, collaborations between musicology and performance are more and more frequent, to the full benefit of both domains. There are historical example of such collaborations that are inspirational. They remind us that both, performance and musicology, live under the same umbrella: it is called music.